URGENSI PENGATURAN CENTRAL BANK DIGITAL CURRENCY (CBDC) DI INDONESIA - Mochamad Ilham Fatahillah (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2020)
Mochamad Ilham Fatahillah, Dr. Budi Santoso, SH., L.LM., Ranitya Ganindha, SH., MH.Fakultas hukum Universitas BrawijayaJl. MT. Haryono No.169 Malange-mail : mochammadil23@gmail.comABSTRAK Tujuan penelitian ini adalah untuk menganalisis urgensi pengaturan central bank digital currency (CBDC) di Indonesia. Mengingat bahwa pengaturan mengenai CBDC mÐ°sih belum Ð°dÐ° sehinggÐ° dibutuhkÐ°n regulÐ°si yÐ°ng mengÐ°tur tentÐ°ng keberÐ°dÐ°Ð°n CentrÐ°l BÐ°nk DigitÐ°l Currency. HÐ°l ini di kÐ°renÐ°kÐ°n regulÐ°si mengenÐ°i uÐ°ng elektronik tidÐ°k mengenÐ°l istilÐ°h BlockchÐ°in sebÐ°gÐ°i sistem penyimpÐ°nÐ°n Ð°kÐ°n tetÐ°pi hÐ°nyÐ° mengenÐ°l server sebÐ°gÐ°i sistem penyimpÐ°nÐ°nnyÐ°. SementÐ°rÐ° server dÐ°n blockchÐ°in memiliki perbedÐ°Ð°n yÐ°ng sÐ°ngÐ°t signifikÐ°n. ÐkÐ°n tetÐ°pi dÐ°lÐ°m hÐ°l proses penerbitÐ°n CBDC lebih tepÐ°t Ð°pÐ°bilÐ° di sÐ°mÐ°kÐ°n dengÐ°n mÐ°tÐ° uÐ°ng fiÐ°t, Ð°kÐ°n tetÐ°pi dÐ°lÐ°m UndÐ°ng-UndÐ°ng Nomor 7 TÐ°hun 2011 tentÐ°ng MÐ°tÐ° UÐ°ng hÐ°nyÐ° menyebut kÐ°n bÐ°hwÐ° mÐ°tÐ° uÐ°ng rupiÐ°h hÐ°nyÐ° dÐ°lÐ°m bentuk kertÐ°s dÐ°n logÐ°m, sementÐ°rÐ° bentuk dÐ°ri CBDC itu sendiri berbentuk digitÐ°l. DÐ°pÐ°t diÐ°rtikÐ°n perlu Ð°dÐ°nyÐ° regulÐ°si bÐ°ru untuk mengÐ°tur CBDC, sehinggÐ° IndonesiÐ° dÐ°pÐ°t menciptÐ°kÐ°n Ð°lÐ°t pembÐ°yÐ°rÐ°n yÐ°ng hÐ°ndÐ°l, Ð°mÐ°n dÐ°n terpercÐ°yÐ°. PenelitiÐ°n ini merupÐ°kÐ°n jenis penelitiÐ°n yuridis normÐ°tif yÐ°ng menggunÐ°kÐ°n metode pendekÐ°tÐ°n perundÐ°ng undÐ°ngÐ°n. KemudiÐ°n PendekÐ°tÐ°n konseptuÐ°l untuk memÐ°hÐ°mi konsep-konsep keberÐ°dÐ°Ð°n CENTRÐL BÐNK DIGITÐL CURRENCY perturÐ°n di indonesiÐ° yÐ°ng dÐ°pÐ°t menjÐ°di lÐ°ndÐ°sÐ°n yuridis Ð°tÐ°s penerbitÐ°n CentrÐ°l BÐ°nk DigitÐ°l Currency (CBDC).Kata kunci: Central Bank Digital Currency, Uang Elektronik, Mata Uang FiatABSTRACT The purpose of this study is to analyze the urgency of regulating central bank digital currency (CBDC) in Indonesia. Bearing in mind that the regulation concerning CBDC is still not yet needed so that the regulations that govern the existence of the Central Currency Currency. This is due to the regulating of electronic devices not about Blockch's term as a storage system, but only about the server, only about the server. While the server and blockchanger have a significant difference. "But in the process of the issuance of the CBDC more than one year ago, it was only in the form of a day, only in the form of it, but it was only in the form at the time. digital. It could be expected that there would only be a new regulation to install CBDC, so that Indonesia could create an additional payment. This research is a type of normative juridical research that uses a short method of bargaining law. Short Steering and the concept to understand the concept of the existence of the Center for Digital CURRENCY CURRENCY is the first of its kind in Indonesia which can become a domain of the Digital Currency (CB) digit.Keywords: Central Bank Digital Currency, Electronic Money, Fiat Currency